Language activities as a platform for second/foreign language learning : its relevance and challenges / Goh Ying Soon ... [et al.] - Goh, Ying Soon; Abdillah, Nasirin; Ibrahim, Noor Aileen; Raja Baniamin, Raja Mariam (Institute of Research, Development and Commercialization (IRDC), 2006)
This study seeks to identify the relevance and challenges faced in conducting language activities to help foster second/foreign language learning at Universiti Teknologi MARA (UiTM) Terengganu. This is also aimed at assisting the organization to review practices of having language activities, hoping this may further cultivate and generate enthusiasm among students to learn second/foreign languages. This research also offers some possible ways to improve students' activities so as to help enhance their second/foreign language learning. In other words, this research may serve as a preliminary attempt aiming at providing reflections and insights on how students' participation in language activities conductedmay be usefulfor them in learning second/foreign languages. The research employs quantitative methodology in which random stratified sampling technique is used Samples consist of Bumiputera students taking English (as a second language) and Mandarin, French, and Arabic classes (as foreign languages). Generally, students are ofthe opinion that language activities can become a significant platform to project andshow their language skills and competency during presentations/performances. Nevertheless, as one ofmany recommendations suggested in the findings of this research, wefound that there is still a needfor evaluation andfo//ow-up work after having participated in the language activities.